2023
DOI: 10.3390/nu15143090
|View full text |Cite
|
Sign up to set email alerts
|

Natural Flavonoids Quercetin and Kaempferol Targeting G2/M Cell Cycle-Related Genes and Synergize with Smac Mimetic LCL-161 to Induce Necroptosis in Cholangiocarcinoma Cells

Thanpisit Lomphithak,
Patthorn Jaikla,
Apiwit Sae-Fung
et al.

Abstract: Cholangiocarcinoma (CCA) is an aggressive cancer associated with a very poor prognosis and low survival rates, primarily due to late-stage diagnosis and low response rates to conventional chemotherapy. Therefore, there is an urgent need to identify effective therapeutic strategies that can improve patient outcomes. Flavonoids, such as quercetin and kaempferol, are naturally occurring compounds that have attracted significant attention for their potential in cancer therapy by targeting multiple genes. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…After the volatilization of alcohol, quercetin dissolved in it will precipitate and is not suitable for clinical use. In recent years, the anti-tumor, antioxidant, and anti-inflammatory effects of quercetin have been increasingly recognized [ 41 ]. Many quercetin dosage forms have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…After the volatilization of alcohol, quercetin dissolved in it will precipitate and is not suitable for clinical use. In recent years, the anti-tumor, antioxidant, and anti-inflammatory effects of quercetin have been increasingly recognized [ 41 ]. Many quercetin dosage forms have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of inhibitors targeting pivotal necroptotic proteins, such as necrostatin-1 (Nec-1), GSK’872 (GSK), and necrosulfamide (NSA), which specifically inhibit RIPK1, RIPK3, and MLKL, respectively, revealed that all inhibitors markedly attenuated cell death provoked by the combination treatment of QUE and the Smac mimetic LCL-161 in cells. These studies indicate the involvement of the RIPK1/RIPK3/MLKL necroptosis pathway after treatment in cholangiocarcinoma cells [ 145 ].…”
Section: Necroptosismentioning
confidence: 99%
“…The results following inhibitors targeting key necroptotic proteins also showed that all inhibitors significantly inhibited cell death induced by combined treatment of KEM with the Smac mimetic LCL-161 in cells. It is concluded that KEM, like QUE, influences the induction of necroptosis via the RIPK1/RIPK3/MLKL pathway [ 145 ].…”
Section: Necroptosismentioning
confidence: 99%
“…To enhance therapy, new therapeutic agents need to be developed to improve the cure rate of DLBCL. Kaempferol is a natural flavonoid with multiple pharmacological activities, including anticancer, anti-inflammatory, and anti-apoptotic effects [5]. Kaempferol has good antibacterial activity, and also has an effect on methicillin-resistant Staphylococcus aureus (MRSA) [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that PI3K/Akt is vital in EBVinduced malignancies. The major EBV oncoprotein latent membrane protein (LMP) 1 and LMP2A activate PI3K/Akt axis, thereby affecting cell survival, apoptosis, and genomic instability [5]. Its downstream target protein is also known to cause cancer, and its role in DLBCL has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%